Metal shrapnel causing psoas abscess: The first case report - Al-Hajjaj, Maher (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: Iliopsoas abscess is defined as the accumulation of suppurative fluid within the fascia surrounding the psoas and iliac muscles. Although some cases reported psoas abscess due to foreign body, to the best of our knowledge this is the first case of metal shrapnel causing psoas abscess. CASE PRESENTATION: A 41 years old male presented to our center after a landmine explosion. After a 24-h of monitoring, he was discharged with no complaints. Later he presented with septicemia, antalgic gait, and low back pain. Computed tomography showed right psoas abscess with metal shrapnel inside. By Anterolateral approach, we drained the retroperitoneal abscess and extracted the metal shrapnel. Follow-up for 6 months revealed no recurrence. CLINICAL DISCUSSION: Iliopsoas abscess is one of the challenging cases that urologists face. We presented a patient with penetrating trauma that led to cause psoas abscess. Computed tomography is considered an excellent imaging study to evaluate such patients. Most cases of psoas abscesses treated with antibiotics and minimally invasive drainage. However, with our case, we performed open surgery to extract the metal shrapnel. CONCLUSION: Psoas abscess with metal shrapnel should be treated emergently. Patients with penetrating trauma should be evaluated strictly. Follow-up is essential in patients with a history of landmine explosion. Psoas abscess with metal shrapnel inside should be treated with broad-spectrum antibiotics and open surgery for drainage.